2019
DOI: 10.2147/opth.s181811
|View full text |Cite
|
Sign up to set email alerts
|

<p>Eye drop emulsion containing 0.1% cyclosporin (1 mg/mL) for the treatment of severe vernal keratoconjunctivitis: an evidence-based review and place in therapy</p>

Abstract: Vernal keratoconjunctivitis (VKC) is a rare, recurrent and multifactorial ocular disease, which typically flares up during spring and affects especially male children and adolescents. This condition does not usually respond to common treatments with antihistamines or mast cells stabilizers, whereas corticosteroids have effective results. Corticosteroids need to be carefully administered, to avoid adverse effects, mainly the secondary development of glaucoma, cataracts, or infections. Immunosuppressive agents, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 63 publications
(68 reference statements)
0
13
0
1
Order By: Relevance
“…Cyclosporine A is a polypeptide derived from the fungi Beauveria nevus and Tolypocladium inflatum , and it is well known for its anti-inflammatory and immunosuppressive effects [ 130 ]. Wang et al demonstrated that CyA attenuates the enhanced expression of IL-1β and TNF-⍺ in the retinas of diabetic rats, probably via the suppression of HMGB1.…”
Section: Future Therapeutic Approachesmentioning
confidence: 99%
“…Cyclosporine A is a polypeptide derived from the fungi Beauveria nevus and Tolypocladium inflatum , and it is well known for its anti-inflammatory and immunosuppressive effects [ 130 ]. Wang et al demonstrated that CyA attenuates the enhanced expression of IL-1β and TNF-⍺ in the retinas of diabetic rats, probably via the suppression of HMGB1.…”
Section: Future Therapeutic Approachesmentioning
confidence: 99%
“…Studies have shown that the symptoms and signs of patients treated with 0.1% CsA improved and steroids were stopped in some patients. [7][8] The efficacy of topical CsA in different dosages and installation frequencies has been shown in several studies. Westland and et al reported three patients with shield ulcers due to VKC who responded quickly with complete reepithelialization after adding topical CsA to conventional treatment including steroids.…”
Section: Discussionmentioning
confidence: 99%
“…The adverse effects associated with the use of corticosteroid eye drops are different. These include elevated intraocular pressure and induced glaucoma, cataract formation, delayed wound healing, and increased susceptibility to infection [57]. Furthermore, the most common reported side effect of CsA is ocular burning, reported in 17% of patients, and approximately 3% of patients stop the medication as a result of this side effect [7].…”
Section: Side Effectsmentioning
confidence: 99%